Nomophobia Among Yarmouk University Students - Momani, Fawwaz; Okour, Sherin (Jordan Journal of Educational Sciences, 2019)
The purpose of this research is to analyze the prevalence of Nomophobia among Yarmouk University students regarding various factors. The Nomophobia Scale (NMP-Q), which was used in this study, was developed by Yildirim (2014), and was adapted into Arabic by the authors. The sample of the study consisted of (1425) students. According to the results of this study, mean scores obtained from the scale demonstrated that the ratio of nomophobia among university students was (15.37%). Besides, female students have higher nomophobia levels compared to male students in terms of gender variable. The results also revealed a positive significant difference between nomophobia levels of university students in terms of the duration of mobile phone ownership variable. A significant difference was found between nomophobia levels of university students in terms of the joint variables (duration of mobile phone ownership and gender). Furthermore, according to results of the analysis, a positive significant difference could not be found between nomophobia level of university students in terms of students living location, college, education level, and the nature of the housing